2013
DOI: 10.3732/ajb.1200653
|View full text |Cite
|
Sign up to set email alerts
|

Genetic patterns of habitat fragmentation and past climate‐change effects in the Mediterranean high‐mountain plant Armeria caespitosa (Plumbaginaceae)

Abstract: A. caespitosa populations exhibit spatial patterns of genetic structure that cannot be explained by the isolation-by-distance model. Shifts along the altitude gradient in response to Pleistocene climatic oscillations and environmentally mediated selective forces might explain the resulting structure and genetic diversity values found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 105 publications
(122 reference statements)
1
15
0
Order By: Relevance
“…(Gómez-Gómez et al 2012), some species of Aquilegia L. (Garrido et al 2012), Armeria caespitosa Boiss. (García-Fernández et al 2013), Borderea chouardii (Li et al 2006), Lamyropsis microcephala (Moris) Dittrich & Greuter (Bacchetta et al 2013); Saxifraga florulenta Moretti (Szövényi et al 2009); S. rivularis Schult. (Guldahl et al 2005); and Rosa subsect.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(Gómez-Gómez et al 2012), some species of Aquilegia L. (Garrido et al 2012), Armeria caespitosa Boiss. (García-Fernández et al 2013), Borderea chouardii (Li et al 2006), Lamyropsis microcephala (Moris) Dittrich & Greuter (Bacchetta et al 2013); Saxifraga florulenta Moretti (Szövényi et al 2009); S. rivularis Schult. (Guldahl et al 2005); and Rosa subsect.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it can be reasonably assumed that the genetic structure is not explained by the model of isolation by distance suggesting alternate factors could influence genetic structure. It has been predicted that geographic distance between populations is not a useful indicator of historical population connectivity or current genetic structure (Arafeh et al 2002;Szövényi et al 2009;Bacchetta et al 2013;García-Fernández et al 2013). Though based on PCoA results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A. caespitosa is self-incompatible [31] and pollinated by bees, bumblebees and syrphid flies [31]. Previous studies on the population genetics of the species revealed relatively low genetic differentiation and a complex genetic structure among populations [40], [41].…”
Section: Methodsmentioning
confidence: 99%
“… Populations have been isolated for long enough to result in genetic differentiation (Segarra‐Moragues et al ., ; Gómez‐Gómez et al ., ; García‐Fernández et al ., ). This pattern results from the combined effects of bottlenecks and genetic drift and/or local adaptation (López‐Pujol et al ., ).…”
Section: Introductionmentioning
confidence: 97%